ANALISIS KINERJA STRUKTUR GEDUNG ASIMETRIS AKIBAT BEBAN GEMPA - Fajar Abdilah; Istiqomah - Istiqomah; Ben Novarro Batubara (Kokoh, 2022)
The infrastucture of high-rise buildings must have an earthquake resistance. As a mitigation effort, a building must be symmetrical. When an earthquake occurs the response of the structure easily predictable. However, along with the development of architectural design, many buildings with irregular shapes (asymmetrical). So, it is necessary to analyze the behavior of structures in irregular buildings. The purpose of this study was to determined the maximum displacement value and  a structural performance due to an earthquake loads based on ATC-40. The earthquake analysis used a Response Spectrum and Time History with the help of ETABS V17.0.1 software, case study located in Bekasi City Government Service Office (POLRES) building.  The research used quantitative descriptive method.  Based on the analysis, the maximum displacement value due to earthquake loads using the Response Spectrum analysis method for the X direction were 74,655 mm and 54,566 mm for the Y direction.